Effects of Eurycoma longifolia standardized extract on female reproductive disposition and perturbation pathways in female rats - Nur Amalina binti Ahmad
Eurycoma longifolia is a traditional plant that has long been used for enhancement of male reproductive functions by enhancement of male testosterone levels thus improving the spermatogenesis process. However, effects of E. longifolia on the female reproductive functions are lacking and have yet to be elucidated. The present work was performed to investigate the potential and beneficial effects of E. longifolia standardized extract, TAF 273, on female reproductive functions and abnormalities. The effects of TAF 273 were investigated in normal female rats and estradiol valerate-induced polycystic ovarian condition rats as well as foetal development and teratogenicity conditions in female rats. Effects of TAF 273 on normal female rats were assessed in female Sprague-Dawley rats, aged between 8 to 10 weeks old. Animals were orally treated with 2.5, 5, 10, 25, 50 and 100 mg/kg of TAF 273 over 5 and 14 days. Oestrous cycle and levels of reproductive hormones were then evaluated together with the histomorphological changes in the ovaries. Similar sets of animals were used for induction of polycystic ovarian syndrome (PCOS) by a single subcutaneous dose of 2 mg estradiol valerate per rat. Rats with vaginal cornification at the end of 60 days were taken to be successfully induced. Treatments with Clomiphene citrate and TAF 273 were administered orally daily for 28 days. The hormonal levels were then measured followed by assessment of histomorphology of the ovary. Steroidogenesis-related genes and proteins (CYP11A1, CYP17A1 and CYP19A1) were also examined in histological paraffin sections using HRP-DAB method and quantitative RT-PCR. Evaluation of foetal development and teratogenicity was done by administration of a single subcutaneous injection of 0.15 mg/kg of estradiol valerate to dams on day 12 of gestation and concurrent treatment with TAF 273 (25, 50 and 100 mg/kg) from day 12 to day 19 of gestation. Foetal assessment was conducted following termination of pregnancy at day 21. The administration of TAF 273 extract did not significantly alter the oestrous cycle of the rats during the 5 and 14 days of treatment which was supported by normal levels of the reproductive hormones as well as normal morphology of the ovaries. TAF 273 extract at a dose of 100 mg/kg also possess beneficial effects in improvement of PCO by improving the ovarian morphology as evident by the presence of more abundant healthy follicles as opposed to cystic follicles and the occurrence of corpora lutea as an indication of ovulation. Hormonal imbalances and expressions of steroidogenic genes were also found to be attenuated probably through its action on oestradiol hormones and CYP19A1 gene. A higher potency of abortion and foetus showing abnormalities in external morphology was observed in female dams exposed to estradiol valerate on GD12. The number of live foetuses in dams treated with 100 mg/kg TAF 273 extract increased but with decreased body weight and crown-rump length of the foetuses. Foetuses with malformations in the form of kyphosis, scoliosis and kinky tail were more pronounced in EV group compared to the control and TAF 273-treatment groups. In conclusion, results obtained showed that the E. longifolia standardized extract, TAF 273, has the potential in maintaining normal functions of the female reproductive system and it may have economic value in the management of female disorders and reproductive health.